The protein c-thrombomodulin mechanism: regulating multiple biological systems - Conway, Edward (Henry Stewart Talks, 2007)
Protein C and thrombomodulin, Mechanisms of action in coagulation and inflammation, Diagnostic and therapeutic insights
Reviewed at 2020/08/12